Can Geographical Indications Support the Indian Village Economy Impacted by the Ongoing Economic Crisis Caused by COVID-19? - A. Mishra (BRICS Law Journal)
The post-COVID-19 economic crisis has resulted in widespread unemployment and the migration of workers in India, particularly in the informal sector, which accounts for more than 90 percent of total employment in the country. Migrant workers are returning to their homes and will soon be looking for alternative sources of income. Entrepreneurship centered on locally made traditional products can provide revenue to migrant workers in such conditions. These returning underprivileged workers can use their traditional knowledge and skills to support their families and create new employment opportunities in their communities. Laws relating to geographical indications will aid in the protection and promotion of such traditional product lines in domestic consumer markets. The protection and promotion of such traditional product lines in domestic consumer markets will be aided by laws relating to geographical indications. The same can be further complemented by the new Geneva Act of the Lisbon Agreement, which went into effect in February 2020 and allows for the registration system of Geographical Indications in multiple countries through a single procedure with the World Intellectual Property Organization. As a result, it is proposed that the government should promote geographical indications as a policy instrument to help the rural economy during these ongoing difficult times.